POSITIVISM AND HISTORICAL-DIALECTICAL MATERIALISM: EPISTEMOLOGICAL INFLUENCES ON BRAZILIAN EDUCATION - Pacheco, Rafael Araujo; Vieira , Mariana Gomide (Seven Editora, 2024)
Epistemology can be understood as the theory of knowledge, establishing a direct link with the ways of constructing and doing Science, with the deepening and understanding of the nature of the Sciences and their paradigms in the various areas of knowledge. The understanding of epistemological currents implies the theoretical and methodological guidance desired in scientific research. In this article, we will address some of the systems of epistemological thought that influenced the process of scientific production in the field of school education: Positivism and Historical-Dialectical Materialism. As a study methodology for such an approach, a literature review was carried out, adopting the approach of narrative review with support, in particular, in Gamboa (2012), Oliveira (2010), Vasconcelos (2017), Triviños (1987) and Saviani (2005), relating the epistemological bases for the construction of theoretical-practical thinking in the context of Education. With regard to Education from a positivist perspective, the influence of Comtean thought in the educational field was perceived through the curricular composition and the institutional organization focused on order and progress. With regard to Historical-Dialectical Materialism in the educational context, Marx's contributions to a popular and transformative Education, aimed at the emancipation of the dominated classes, judging the need for a distancing from traditional Education in elitist molds, is significant. DOI:https://doi.org/10.56238/sevened2024.033-011